Asymmetric Central Processing of Sensory Stimuli in Idiopathic Focal Dystonia - R. A. Grünewald; J. Shipman; Y. Yoneda; H. J. Sagar (Behavioural Neurology)
Idiopathic torsion dystonia is characterized by persistent abnormalities of posture. We tested the hypothesis that abnormal sensorimotor processing is involved pathophysioiogically by looking for asymmetry of sensory processing in patients with asymmetric symptoms. Sixteen patients with torticollis (ten with head turning to the right and six to the left), seven with simple writer's cramp and 19 healthy control subjects were tested. The tasks involved matching one of five lengths of stick or weights presented to one hand with sticks and weights chosen by the other hand. All experiments were performed with the subject blindfolded. Patients with torticollis tended to underestimate weights presented to the hand away from which the head tended to turn. Control subjects showed no significant tendency to overestimate or underestimate lengths or weights with either hand, and dystonic patients showed no tendency to overestimate or underestimate lengths. Those with writer's cramp underestimated weights when the stimulus was presented to the affected hand. An asymmetry can thus be detected in muscles remote from the site of dystonia, indicating a generalized abnormality of sensorimotor processing.